Analisis faktor-faktor yang mempengaruhi produksi singkong di Kota Salatiga - Purnomo, Didit; Kusuma, Mahanara Puja (Journal of Economics Research and Policy Studies, 2022)
This study aims to analyze the effect of land area, fertilizer, and labor on cassava production in Argomulyo District, Salatiga City. This type of research is called quantitative research. The study was conducted in the Argomulyo District, Salatiga City. The population in this study were all farmers who planted cassava in the Argomulyo District of Salatiga City with rice fields, fields, and gardens. The research sample of 100 respondents was selected with random sampling techniques. Data collection techniques with a questionnaire. Data analysis techniques with multiple linear regression analysis and the classic assumption test. The results show that land area significantly affects cassava production in the Argomulyo District of Salatiga City. Fertilizer significantly affects cassava production in the Argomulyo District of Salatiga City. Labor has a significant effect on cassava production in Argomulyo District, Salatiga.